2020
DOI: 10.1080/11101849.2020.1768630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial sleep deprivation following night shift on cognitive functions of Egyptian anesthesiologists; prospective observational study

Abstract: Background: Anesthesiologists in Egypt as a representative of developing countries with large populations and shortage of trained personnel and extended working hours that may reach 30 continuous hours are susceptible victims of fatigue and sleep deprivation. Objectives: To evaluate and compare differences in cognitive function of anesthesia residents before and after the 24 hours work shift. Methods: Prospective, observational, cohort study that was conducted in tertiary care hospital (Kasr El-Aini Hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Among 64 studies included in the systematic review, 39 were related to the effect of shift work on cognitive functions ( Table 4 ) ( Deary and Tait, 1987 ; Orton and Gruzelier, 1989 ; Lingenfelser et al, 1994 ; Smith et al, 1995 ; Petru et al, 2005 ; Rouch et al, 2005 ; Saricaoğlu et al, 2005 ; Griffiths et al, 2006 ; Chang et al, 2011 , 2013a , b ; Anderson et al, 2012 ; Shwetha and Sudhakar, 2012 , 2014 ; Niu et al, 2013 ; Özdemir et al, 2013 ; Veddeng et al, 2014 ; Kazemi et al, 2016 , 2018 ; Maltese et al, 2016 ; Titova et al, 2016 ; Vajravelu et al, 2016 ; Haidarimoghadam et al, 2017 ; Soares and de Almondes, 2017 ; Williams et al, 2017 ; Persico et al, 2018 ; Taylor et al, 2019 ; Abdelhamid et al, 2020 ; Adams and Venter, 2020 ; Athar et al, 2020 ; James et al, 2021 ; Prasad et al, 2021 ; Stout et al, 2021 ; Sun et al, 2021 ; Zhao et al, 2021 ; An et al, 2022 ; Benítez-Provedo et al, 2022 ; Esmaily et al, 2022 ; Peng et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 64 studies included in the systematic review, 39 were related to the effect of shift work on cognitive functions ( Table 4 ) ( Deary and Tait, 1987 ; Orton and Gruzelier, 1989 ; Lingenfelser et al, 1994 ; Smith et al, 1995 ; Petru et al, 2005 ; Rouch et al, 2005 ; Saricaoğlu et al, 2005 ; Griffiths et al, 2006 ; Chang et al, 2011 , 2013a , b ; Anderson et al, 2012 ; Shwetha and Sudhakar, 2012 , 2014 ; Niu et al, 2013 ; Özdemir et al, 2013 ; Veddeng et al, 2014 ; Kazemi et al, 2016 , 2018 ; Maltese et al, 2016 ; Titova et al, 2016 ; Vajravelu et al, 2016 ; Haidarimoghadam et al, 2017 ; Soares and de Almondes, 2017 ; Williams et al, 2017 ; Persico et al, 2018 ; Taylor et al, 2019 ; Abdelhamid et al, 2020 ; Adams and Venter, 2020 ; Athar et al, 2020 ; James et al, 2021 ; Prasad et al, 2021 ; Stout et al, 2021 ; Sun et al, 2021 ; Zhao et al, 2021 ; An et al, 2022 ; Benítez-Provedo et al, 2022 ; Esmaily et al, 2022 ; Peng et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“… Abdelhamid et al (2020) evaluated the differences in cognitive functions among 50 anaesthesia residents before and after a 24-h shift and found that after the shift their cognitive processes were impaired. Adams and Venter (2020) wanted to quantify the effects of shift work on cognitive functions in anaesthesiology trainees and observed that after 14-h night shift they had a decline in reaction time, psychomotor functions and attention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even acute exposure to sleep deprivation affects the cognitive performance of health personnel. Egyptian anesthesiologists exposed to 24-hour working shifts had increased daytime sleepiness and RTs and performed poorly on tasks that assess alertness, problem-solving, psychomotor skills, attention, and mental flexibility [18].…”
Section: Discussionmentioning
confidence: 99%